2021
DOI: 10.3390/antibiotics10070769
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Non-β-Lactam β-Lactamase Inhibitors

Abstract: The growing emergence of drug-resistant bacterial strains is an issue to treat severe infections, and many efforts have identified new pharmacological agents. The inhibitors of β-lactamases (BLI) have gained a prominent role in the safeguard of beta-lactams. In the last years, new β-lactam–BLI combinations have been registered or are still under clinical evaluation, demonstrating their effectiveness to treat complicated infections. It is also noteworthy that the pharmacokinetics of BLIs partly matches that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 105 publications
1
11
0
Order By: Relevance
“…Despite the scarcity of data, new beta-lactamase inhibitors can diffuse into the ELF [ 92 , 93 ], and this feature is important for their use in combination with beta-lactams [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scarcity of data, new beta-lactamase inhibitors can diffuse into the ELF [ 92 , 93 ], and this feature is important for their use in combination with beta-lactams [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, it has been noticed that β-lactam-BLI combinations require a high concentration of either of the components for the desired activity in in-vivo studies, which can lead to toxicity or undesirable pharmacological outcomes (Papp-Wallace, 2019). Additionally, many BLIs exhibit low oral absorption, especially in their native form, and demand chemical modifications to stabilize them and exhibit better oral absorption (Luci et al, 2021). For instance, sulbactam in its native form was identified to have poor oral absorption as compared to pivaloyloxymethyl ester of sulbactam (Campoli-Richards and Brogden, 1987).…”
Section: Challenges Of Taking β-Lactam Potentiators From Bench To Bed...mentioning
confidence: 99%
“…or unbound AUC/MIC (fAUC/MIC). [14][15][16][17] Another DBO-BLI, avibactam, has slow but reversible binding making time above the critical concentration (T > C T ), the index that most closely explains its activity. 18 Comparatively, irreversible inhibitors such as vaborbactam and relebactam rely on concentration and time exposure for target attainment where fAUC/MIC is a more accurate index.…”
Section: Durlobactammentioning
confidence: 99%
“…Consistent with previous phase I studies, SUL-DUR was largely well-tolerated among the subjects with no clinically meaningful differences in safety data. [14][15][16]39 Another phase I study evaluated patients with mild, moderate, and severe RI who were treated with SUL-DUR. It was found that RI did not increase the risk of having an AE.…”
Section: Safe T Y and Toler Ab Ilit Ymentioning
confidence: 99%